Recent developments in lead-free bismuth-based halide perovskite nanomaterials for heterogeneous photocatalysis under visible light. Issue 12 (9th March 2023) - Wu, Zehong; Tüysüz, Harun; Besenbacher, Flemming; Dai, Yitao; Xiong, Yujie
Abstract : This mini-review presents a brief overview of recent progress in bismuth-based halide perovskite (BHP) nanomaterials for heterogeneous photocatalysis under visible light, including the synthesis and physical–chemical properties of advanced BHPs. Abstract : Halide perovskite materials, especially lead-based perovskites, have been widely used for optoelectronic and catalytic applications. However, the high toxicity of the lead element is a major concern that directs the research work toward lead-free halide perovskites, which could utilize bismuth as a promising candidate. Until now, the replacement of lead by bismuth in perovskites has been well studied by designing bismuth-based halide perovskite (BHP) nanomaterials with versatile physical–chemical properties, which are emerging in various application fields, especially heterogeneous photocatalysis. In this mini-review, we present a brief overview of recent progress in BHP nanomaterials for photocatalysis under visible light. The synthesis and physical–chemical properties of BHP nanomaterials have been comprehensively summarized, including zero-dimensional, two-dimensional nanostructures and hetero-architectures. Later, we introduce the photocatalytic applications of these novel BHP nanomaterials with visible-light response, improved charge separation/transport and unique catalytic sites. Due to advanced nano-morphologies, a well-designed electronic structure and an engineered surface chemical micro-environment, BHP nanomaterials demonstrate enhanced photocatalytic performance for hydrogen generation, CO2 reduction, organic synthesis and pollutant removal. Finally, the challenges and future research directions of BHP nanomaterials for photocatalysis are discussed.